The Longitudinal Emergency Medical Technician (EMT) Attributes and Demographics Study (LEADS): The First 10 Years and a Look at Public Perception of Emergency Medical Services (EMS). (24th November 2016) - Crowe, Remle P.; Bentley, Melissa A.; Levine, Roger
Abstract : RP Crowe, MA Bentley, R Levine .The Longitudinal Emergency Medical Technician (EMT) Attributes and Demographics Study (LEADS): the first 10 years and a look at public perception of Emergency Medical Services (EMS) .Prehosp Disaster Med .2016 ;31 (Suppl.1 ):s1 –s6 .